HUBUNGAN DUKUNGAN SOSIAL DENGAN STRES PADA LANSIA YANG TINGGAL DIPANTI TRESNA WERDHA ILOMATA KOTA GORONTALO - Salahuddin Liputo; Anik Indarwati (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The increasing number of elderly the increasing number of health problems faced by the researcher. The social support in needed by the elderly who lived in panti werdha. The social support can affect the stress. The research aimed to find out the relationship between social support and stress of elderly lived in panti trisna werdha ILOMATA of gorontalo city. Design of research was Cross Sectional descriptive correlation. The population of research was elderly in gorontalo city amounted to 35 people. The technique of sampling was total sampling. The data analysis was done though several steps such as (1) Univariat analysis by using frequency distribution, and (2) Bivariat analysis to observe the relationship between variables. By applying Chi Square, it obtained to 0,002 (p<0.02) meant the there was a relationship between social support toward stress of elderly lived in panti trisna werdha “ILOMATA” of gorontalo city. To conclude, social support has a significant relationship with stress of elderly who lived at home for elderly. Almost of elderly did not get a social support, so that almost of them got a high stress. Therefore. It suggests to the family and panti trisna werdha ilomata of gorontalo city, to give a good service to the elderly and to fulfill their needs.